Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.coi.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Immunological responses to influenza vaccination: lessons for improving vaccine efficacy

Abstract: A critical factor in the maturation of influenza vaccine responses is the nearly inevitable binding of vaccine antigens by exiting anti-influenza IgGs. These antigen-IgG immune complexes direct the response to immunization by modulating cellular processes that determine antibody and T-cell repertoires: maturation of dendritic cells, processing and presentation of antigens to T cells, trafficking of antigens to the germinal center, and selection of B cells for antibody production. By focusing on the recent adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…This phenomenon has been referred to as ‘original antigenic sin’ (OAS) 911 and is especially relevant in the context of annual infections and vaccinations with drifting and shifting influenza viruses. 12,13 Also in the case of flaviviruses, OAS phenomena can play an important role, 14,15 as a result of sequential exposures to flaviviruses that co-circulate in the same geographical regions, global travel-related exposures, and/or immunization with different flavivirus vaccines, which is the topic of the present work.…”
Section: Introductionmentioning
confidence: 95%
“…This phenomenon has been referred to as ‘original antigenic sin’ (OAS) 911 and is especially relevant in the context of annual infections and vaccinations with drifting and shifting influenza viruses. 12,13 Also in the case of flaviviruses, OAS phenomena can play an important role, 14,15 as a result of sequential exposures to flaviviruses that co-circulate in the same geographical regions, global travel-related exposures, and/or immunization with different flavivirus vaccines, which is the topic of the present work.…”
Section: Introductionmentioning
confidence: 95%
“…Type II FcγRs engage ICs containing sialylated IgG Fc domains, which can result in anti‐inflammatory activity [via DC‐SIGN during intravenous immunoglobulin (IVIG) therapy] or high‐affinity antibody production (via B‐cell CD23 engagement) . Increased sialylation correlates with greater antibody affinity following human influenza vaccination . It has been proposed that influenza vaccination results in the production of sialylated anti‐HA IgG antibodies by plasmablasts, which form ICs with vaccine antigen .…”
Section: Fc‐mediated Effector Functions Of Antibodies and Fcrsmentioning
confidence: 99%
“…It has been proposed that influenza vaccination results in the production of sialylated anti‐HA IgG antibodies by plasmablasts, which form ICs with vaccine antigen . The sialylated ICs are delivered to lymph node germinal centers by subcapsular macrophages and noncognate B cells through interactions with CD23 . Sialylated ICs may associate with follicular dendritic cells prolonging contact between B cells and influenza antigen, driving affinity maturation of antibodies in the germinal center (GC) .…”
Section: Fc‐mediated Effector Functions Of Antibodies and Fcrsmentioning
confidence: 99%
“…Zhang et al [60] demonstrated that Abs enter GCs, bind antigen held on FDCs, and compete with GC B cells in an affinity-dependent way. Through these mechanisms, Abs derived from preexisting MBCs could facilitate affinity maturation of responses to drifted epitopes on the HA head [61]. In the case of MBC-derived anti-stalk Abs, GC B cell selection would be shifted towards targeting the immunodominant HA head [62].…”
Section: Regulation Of the Anti-ha Response By Mbc-derived Antibodiesmentioning
confidence: 99%